Racial Differences in the Prognosis and Survival of Cutaneous Melanoma From 1990 to 2020 in North America: A Systematic Review and Meta-Analysis. Issue 2 (March 2022) - Lam, Megan; Zhu, Jie Wei; Hu, Angie; Beecker, Jennifer
Background: Factors influencing the difference in the diagnosis and treatment of melanoma in racial minority groups are well-described in the literature and include atypical presentations and socioeconomic factors that impede access to care. Objective: To characterize the differences in melanoma survival outcomes between non-Hispanic white patients and ethnic minority patients in North America. Methods: We conducted searches of Embase via Ovid and MEDLINE via Ovid of studies published from 1989 to August 5, 2020. We included observational studies in North America which reported crude or effect estimate data on patient survival with cutaneous melanoma stratified by race. Results: Forty-four studies met our inclusion criteria and were included in this systematic review. Pooled analysis revealed that black patients were at a significantly increased risk for overall mortality (HR 1.42, 95% CI, 1.25-1.60), as well as for melanoma-specific mortality (HR 1.27, 95% CI, 1.03-1.56). Pooled analyses using a representative study for each database yielded similar trends. Other ethnic minorities were also more likely report lower melanoma-specific survival compared to non-Hispanic white patients. Conclusion: Our results support findings that melanoma patients of ethnic minorities, particularly black patients, experience worse health outcomes with regards to mortality. Overall survival and melanoma-specific survival are significantly decreased in black patients compared to non-Hispanic white patients. With the advent of more effective, contemporary treatments such as immunotherapy, our review identifies a gap in the literature investigating present-day or prospective data on melanoma outcomes, in order to characterize how current racial differences compare to findings from previous decades.